Fabrication of automative body part using carbon fiber - Muhammad Naqeeb, Meor Ruslan (2013)
This thesis presents the fabrication of automotive part using carbon fiber. In this modern era, carbon fiber became high demand in the market. This is because sports like racing such as sport car racing, motorcycle racing and bicycle racing become famous. So carbon fiber became popular among the racer because carbon fiber is strong, light at once can reduce the part of automotive and increase the speed of vehicle. Beside carbon fiber do not rust and the out layer is interesting. The project has to begin with choosing 4 automotive parts. The selected parts are side mirror, box, motor cycle body part and oil tank cover. These parts consist of different shape which is flat, curve and flat curve. Based on that, the difficulty of fabricate this project can be determined. These parts have designed using SolidWork engineering drawing software for the structural threedimensional solid modeling. All the step and procedure of fabricate the glass fiber and carbon fiber was listed in this thesis. The problem faced during making this project and the problem solving also have in this thesis. Lastly, for making the product better and perfect the recommendation for the future work was been discussed in this thesis.